Особливості системи адаптації мережевих структур промислових підприємств - Мехович, Сергій Анатолійович; Сікєтіна, Наталія Геннадіївна (Класичний приватний університет, 2019)
Статтю присвячено актуальним питанням адаптації промислових підприємств під впливом мінливого конкурентного середовища. Досліджено теоретичні питання економічних категорій "адаптація", "адаптаційний процес", "адаптаційна система" та "адаптаційний механізм" відносно промислових підприємств. Виділено чотири типи адаптивних механізмів в основі аналізу літературних джерел. Визначено три адаптаційні стратегії щодо промислових підприємств. Досліджено адаптаційні чинники в мережевій структурі підприємства і розділено їх на чинники зовнішнього та внутрішнього впливу. Розглянуто зміст та структуру адаптаційної стратегії промислового підприємства. в мінливих умовах. Визначено механізм адаптаційної системи мережевого формування. Окреслено структуру механізму адаптаційної системи мережевого формування.

Since the objective evaluation of competitiveness of products of the industrial enterprise’ values is one of the key factors affecting the definition of the economic effectiveness of systems of adaptation of production-innovation clusters, the issue is widely explored in the writings of representatives of various economic schools. In Ukraine, in the context of a worsening economic situation, the problems of increasing the effectiveness of industrial enterprises’ activity become especially urgent. Effective solutions to such problems contribute to the growth of the national economy and increase in its investment attractiveness as well. The main objective of the article is to study and generalize theoretical and methodological aspects of the theory of adaptation and adaptation process of domestic enterprises for their further development. The specific socio-economic reality of domestic industrial enterprises is variable, diverse and complex. These properties of economic reality are the main causes of the difficulties of its scientific knowledge. The extremely changing nature of the market environment distorts market conditions, when traditional methods of conducting economic activity no longer guarantee the maintenance of the acquired market positions. New approaches to defining development strategies from the mission are needed, and the search for mechanisms for adapting to emerging changes. The current conditions of industry activity in Ukraine do not meet the strict norms of an effective western market. As you know, the process of forming market relations in Ukraine has its own characteristics and is characterized by a high degree of asymmetry regarding the potential of production of competitive products. It may induce individual industrial enterprises to make it impossible to produce competitive products. The authors believe that it is expedient to introduce the meaning of "adaptive system of network formation", since it tends to be quantified by the result of the influence of the process of forming the network structure of the enterprise on the efficiency of its activities by creating a mechanism for the targeted creation of competitive corporate (cluster) benefits in a specific segment of the market, which includes organizational, structural, technological, engineering, economic, financial and marketing measures at the enterprises and institutions of the members of the network form nets with regional authorities and research intended to achieve the mission and goals. The proposed definitions can be used to create a system for adapting the network structure of an industrial enterprise in a changing competitive environment. Unlike a number of the above approaches, the approach of the authors of this article deals with the system of adaptation of the network structures of the industrial enterprise, taking into account the influence of external factors. Thus, enterprises developing an adaptive network formation system form direct cluster advantages over a certain segment of the market.
Features adaptation systems of industrial enterprises networking structures
Keywords: адаптація; адаптаційний процес; адаптаційне управління; підприємство; стратегія; механізм; adaptation; adaptation process; enterprise; adaptation management; strategy; mechanism